Road traffic injuries in northern Laos: trends and risk factors of an underreported public health problem - Slesak, Günther; Inthalath, Saythong; Wilder-Smith, Annelies; Barennes, Hubert (Tropical medicine & international health, 2015)
Objectives Road traffic injuries (RTI) have become a leading cause for admissions at Luang Namtha Provincial Hospital (LNPH) in rapidly developing northern Laos. Objectives were to investigate trends, risk factors and better estimates of RTI. Methods Repeated annual surveys were conducted with structured questionnaires among all RTI patients at LNPH from 2007 to 2011. Hospital and police data were combined by capture-recapture method. Results The majority of 1074 patients were young [median 22 years (1-88)], male (68%), motorcyclists (76%), drove without licence (85%) and without insurance (95%). Most accidents occurred during evenings and Lao New Year. Serious motorbike injuries were associated with young age (1-15 years), male sex (OR 2.2, 95% CI 1.1-4.6) and drivers (OR 2.1, 95% CI 1.1-4.3); more serious head injuries with alcohol consumption (OR 2.5, 95% CI 1.7-3.7), male sex (OR 2.3, 95% CI 1.4-3.7) and no helmet use (OR 2.0, 95% CI 1.2-3.4). No helmet use was associated with young age, time period, pillion passengers (OR 2.7, 95% CI 1.6-4.7), alcohol (OR 1.9, 95% CI 1.2-2.8) and no driver license (OR 2.0; 95% CI 1.1-3.4). Main reasons not to wear helmets were not possessing one, and being pillion passenger. Capture-recapture analysis showed four times higher RTI estimates than officially reported. Mortality rate was 11.6/100.000 population (95% CI 5.1-18.1/100.000). Conclusions RTI were substantially underestimated. Combining hospital with police data can provide better estimates in resource-limited settings. Preventive programmes and law enforcement have to target male drivers, alcohol, licensing and helmet use, especially among children and pillion passengers. Increased efforts are needed during evening time and special festivals.